Desire for Smart Growth: A Survey of Residential Preferences in the Salt Lake Region of Utah - Tian, G.; Ewing, R.; Greene, William (2015)
© 2015, © 2014 Virginia Polytechnic Institute and State University.As an alternative to sprawling development, smart growth combines proximity to work, proximity to shopping and other destinations, neighborhood housing mix, shared and paid parking, complete street designs, and proximity to public transit. This article uses a stated-choice experiment to determine residents' attitudes toward these various aspects of smart growth in the Salt Lake region of Utah. Utah is a conservative state, where attitudes toward auto-oriented suburbia may be more positive than in other parts of the United States. So, one might wonder whether changing national attitudes toward smart growth, documented in several surveys, apply to residents of the Salt Lake region. In this stated-choice experiment, respondents were asked to choose between pairs of housing scenarios with different attributes and different prices. Mixed logit (random parameters logit) was used to relate individuals' choices to attributes, prices, and sociodemographic characteristics of respondents. The results show that, generally, respondents have positive attitudes toward most aspects of smart growth but still express preferences for single-family neighborhoods with free parking in their own driveways or garages. Different life cycle cohorts have different preferences. Proximity to work is more important for childless young adults. Young families with children place higher value on living in a neighborhood with only single-family homes and transit access. Retired empty nesters favor a mix of housing types over single-family housing on one-acre-plus lots. The results suggest that while residents of the Salt Lake region like suburban neighborhoods with primarily single-family houses, they would also like to have improved accessibility to amenities in the suburbs.